Hepatitis E virus infections among patients with acute febrile jaundice in two regions of Cameroon: First molecular characterization of hepatitis E virus genotype 4. - Abdou Fatawou Modiyinji; Lange Tchamba Amorgathe Tankeu; Chavely Gwladys Monamele; Moise Henri Yifomnjou Moumbeket; Paul Alain Tagnouokam Ngoupo; Huguette Tchetgna Simo; Abanda Njei Ngu; Kazanji Mirdad; Richard Njouom (PLoS ONE, 2024)
Background Febrile jaundice is a common indicator of certain infectious diseases, including hepatitis E. In Cameroon, the yellow fever virus is the only pathogen that is monitored in patients who present with this symptom. However, more than 90% of the samples received as part of this surveillance are negative for yellow fever. This study aimed to describe the prevalence and hepatitis E virus (HEV) genotype among yellow fever-negative patients in the Far North and West regions of Cameroon. Methods In a cross-sectional study, yellow fever surveillance-negative samples collected between January 2021 and January 2023 were retrospectively analyzed. Anti-HEV IgM and IgG antibodies were tested using commercially available ELISA kits. Anti-HEV IgM and/or IgG positive samples were tested for HEV RNA by real-time RT-PCR, followed by nested RT-PCR, sequencing and phylogenetic analysis. Results Overall, 121 of the 543 samples (22.3%, 95% CI: 19.0% - 26.0%) were positive for at least one anti-HEV marker. Amongst these, 8.1% (44/543) were positive for anti-HEV IgM, 5.9% (32/543) for anti-HEV IgG, and 8.3% (45/544) for both markers. A total of 15.2% (12/79) samples were positive for HEV RNA real-time RT-PCR and 8 samples were positive for HEV RNA by nested RT-PCR. Phylogenetic analysis showed that the retrieved sequences clustered within HEV genotypes/subtypes 1/1e, 3/3f and 4/4b. Conclusion Our results showed that HEV is one of the causes of acute febrile jaundice in patients enrolled in the yellow fever surveillance program in two regions of Cameroon. We described the circulation of three HEV genotypes, including two zoonotic genotypes. Further studies will be important to elucidate the transmission routes of these zoonotic HEV genotypes to humans in Cameroon.